Changes in strengthening mechanisms in creep of 9Cr-1.8W-0.5Mo-VNb steel tested over wide ranges of creep conditions. (April 2021) - Maruyama, Kouichi; Sekido, Nobuaki; Yoshimi, Kyosuke
Abstract: The present paper studies stress, temperature and heat dependence of creep rupture life of 9Cr-1.8W-0.5Mo-VNb (Gr. 92) steel with creep rupture data of 4 heats reported in National Institute for Materials Science Creep Data Sheet 48B. In creep of Gr. 92 steel there are four regions, H, M, L and G, showing different stress and temperature dependence of creep rupture life. Creep rupture life of Gr. 92 steel increases with increasing hardness after tempering in Regions H and M (high and medium stress), and with increasing prior austenite grain size in long-term Region G. Its creep rupture life is insensitive to the heats in low-stress Region L. Creep rupture lives of the steel are formulated in each region as a function of stress, temperature and a metallurgical variable determining its creep rupture life. Two types of breakdown in creep strength (substantial decrease in stress exponent for creep rupture life) take place in Gr. 92 steel; one from Region M to Region L, and the other from Region M or L to Region G. Since Gr. 92 steel is used in Region G in steam power boilers, the second breakdown to Region G is of engineering importance. Causes of the second breakdown are discussed with creep rupture data of four grades of creep strength enhanced ferritic steels. Highlights: Small grain size is detrimental in creep of creep strength enhanced ferritic steels. Grade 91 steel is as strong as grade 92 steels with increased amounts of w and B. Strengthening mechanism of creep is elucidated in the time range over 100, 000 h. Creep rupture life is formulated in the time range over 100, 000 h. Two breakdowns of creep strength occur in creep strength enhanced ferritic steels.